2017
DOI: 10.1155/2017/1538750
|View full text |Cite
|
Sign up to set email alerts
|

Association of Platelet Membrane Glycoprotein HPA-2a/b, GP VI T13254C, and GP IbαVNTR Polymorphisms with Risk of Coronary Artery Disease: A Meta-Analysis

Abstract: Background and Aims Recently, controversial results have been reported regarding the association of the polymorphisms of platelet membrane glycoproteins (HPA-2a/b, GP VI T13254C, and GP Ibα VNTR) with coronary artery disease (CAD). We performed this meta-analysis to further assess the polymorphisms of platelet membrane glycoproteins with a risk of CAD. Methods A systematic electronic literature search was conducted in Embase, Cochrane Library, PubMed, and the Chinese Biomedical Literature Database (CBM). Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thus so far a large number of case-control studies highlighted the association between platelets glycoproteins SNPs and CAD susceptibility. Yet, these associations fail to be confirmed when reassessed on a larger sample sized meta-analysis, therefore raising doubts on the robustness of these evidences (15).…”
Section: Platelets Glycoproteinsmentioning
confidence: 95%
“…Thus so far a large number of case-control studies highlighted the association between platelets glycoproteins SNPs and CAD susceptibility. Yet, these associations fail to be confirmed when reassessed on a larger sample sized meta-analysis, therefore raising doubts on the robustness of these evidences (15).…”
Section: Platelets Glycoproteinsmentioning
confidence: 95%
“…They reported that the frequency of HPA-2a/2b and HPA-2b/2b genotypes had a significant relationship with the incidence of the disease. Nonetheless, a meta-analysis of 25 case–control studies demonstrated a significant association between HPA-2b allele and HPA-2a/2b and HPA-2b/2b genotypes with incidence of CAD [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%